Understanding Newspaper Coverage On E-Sports In Malaysia - Norizam, Afif Emir; Ismail, Muhammad Arif; Md Noor, Muhammad Noor Hariz; Abd Aziz, Siti Hajar; Mohd Azni, Zuliani (2020)
E-sports, a form of competition using video for multiplayer video games, particularly among professional players as individually as teams is very fast developing in Malaysia. According to British Broadcasting Corporation, e-sport international sales almost triple its global audience to nearly 600 million people by 2020. The study aimed at understanding the newspaper role in creating the awareness of e-sport in Malaysia. In-depth interview was done and recorded digitally with E-Sports Malaysia (ESM) Head of Communication Muhammad Farouq Abdul Patah as the main respondent. The study found out that traditional media has increase their interest on e-sports since year 2018 and many positive coverages has been given to it to improve people initial perception about e-sports which was earlier deemed as wasteful activities. The newspaper has been considered as a medium which provide better facts regarding e-sports and mobile gaming in compared with social media. Today, with the help of newspapers, older and new generation as beginning to accept e-sports as a skill sport with the ability to generate income, strengthening unity and bridging cultural barriers, as well as create new opportunity for business and careers. This study has fully maximised the use of videography and editing to understand this issue and their result is ready to be uploaded as an e-content in the respected digital platform to disseminate awareness on the topic.